Efektifitas Skin Wrap dalam Mencegah Hipotermia pada Kelahiran Bayi Prematur - Casman, Casman (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2018)
ABSTRACT Objective: to investigate the effectiveness of skin wraps in preventing hypothermia on newborn of premature infants. Method: study litetarure was selected which the articles were taken from the database ScienceDirect, Wiley dan Scopus. Articles were retrieved using the following keywords: skin wrap and premature infants. Result: one article didn’t proved that the use of plastic was uneffective at maintaining the premature infant's body temperature (p = 0.07). The average plastic could use of non sterile plastics and wraping to the premature infant's body imedietly after newborn without drying body. The plastic attachment could be all over the body and head or covering up the neck. Conclusions: the use of plastic immediately after birth with vynil isolation bag or polyethylene plastic effective for preventing heat loss in premature infants.